2021
DOI: 10.1111/jocd.14337
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous findings in patients with chronic venous insufficiency

Abstract: Background Venous hypertension causes many different cutaneous findings such as varicosities, telangiectasia, edema, and pigmentation, dermatitis, and venous ulcers on the skin. Objective This study aims to investigate the cutaneous signs and symptoms of chronic venous insufficiency (CVI) and to examine their contribution to early diagnosis. Methods A total of 150 patients were included in the study who applied to the dermatology outpatient clinic and were diagnosed with skin disease related to CVI or had skin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 25 publications
0
5
0
2
Order By: Relevance
“…Tiwary et al [ 50 ] observed pigmentation and eczema in 24% of cases and stated that the severity of the disease increased with the severity of the pigmentation. Moreover, according to a recent study, pigmentation (19.3%) was identified as one of the most common skin findings observed in patients with CVI, diabetes, hyperlipidemia, and thyroid disease [ 51 ]. In our study, 40.3% and 41.9% of patients had a severe and moderate SP score, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Tiwary et al [ 50 ] observed pigmentation and eczema in 24% of cases and stated that the severity of the disease increased with the severity of the pigmentation. Moreover, according to a recent study, pigmentation (19.3%) was identified as one of the most common skin findings observed in patients with CVI, diabetes, hyperlipidemia, and thyroid disease [ 51 ]. In our study, 40.3% and 41.9% of patients had a severe and moderate SP score, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Neben Stauungsdermatitis sind es beispielsweise asteatotische Ekzeme oder allergische Kontaktekzeme. 73 Die Prävalenz relevanter Kontaktsensibilisierungen ist bei Patienten mit UCV erhöht, so dass bei entsprechendem Verdacht eine weiterführende Diagnostik mit Epikutan-Testungen und/oder repetitivem offenem Applikationstest (ROAT) erfolgen sollte. 74,75 Patientenedukation und Selbstmanagement Das Wissen um die eigene Erkrankung und grundlegende Kenntnisse der Behandlung einschließlich deren durchzuführende Maßnahmen sowie der dabei zum Einsatz kommenden Materialien, ermöglicht den Patienten mit UCV ein besseres Therapieverständnis zu entwickeln und fördert somit die Adhärenz.…”
Section: ↔ Starker Konsens (100%)unclassified
“…Apart from stasis dermatitis, these include asteatotic eczemas or allergic contact eczemas. 73 Given the increased prevalence of relevant contact sensitizations in patients with VLU, advanced diagnostics with patch testing and/or repeated open application test (ROAT) should be performed in case of suspicion. 74,75 Patient education and self-management Knowledge about their own disease and basic knowledge about the treatment, including the measures to be taken and the materials utilized for this purpose, enables patients with VLU to develop a better understanding of the therapy and thus promotes adherence.…”
Section: Recommendation 64 Strength Agreementmentioning
confidence: 99%